UJI BANDING RESPON HEMODINAMIK PADA INTUBASI ENDOTRAKHEA SETELAH PEMBERIAN FENTANYL 1 Î¼G/KGBB DAN FENTANYL 2 Î¼G/KGBB INTRAVENA DENGAN INDUKSI PROPOFOL 2 MG/KGBB INTRAVENA - , CECEP HIDAYAT, Dr. IG. Ngurah Rai Artika, Sp.An.K. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Endotracheal intubation laringoscopy often caused the increase in both sympathetic and simpatoadrenal activities. Some drugs have been used to reduce the response, such as local anesthetics, beta blocker, alpha-2 blocker and vasodilator. Fentanyl was the drug chosen to reduce cardiovascular fluctuation. The study aimed at comparing the use of fentanyl 2 ug/kgwb intravena and fentanyl 1 uk/kgwb intravena and propophol 2 mg/kgwb intravena induction in reducing the cardiovascular fluctuation caused by laryngoscopic intubation. It employed blinded and randomized clinical test with 120 subjects of the patients with the physical stauts of ASA I and II who were planned to undergo elective operation under general anesthesi in RS. Dr. Sardjito Yogyakarta. They were assigned to two groups of 60 patients. Group I was given Fentanyl 1 ug/kgwb intravena and Group II was given Fentanyl 1 ug/kgwb intravena before laryngoscopic intubation. All of the patients were given Midazolam 0.05 mg/kgwb intravena and the induction was initiated using propofol 2 mg/kgwb intravena with Rocuronium intubation facility 0.6 mg/kgwb intravena and it was maintained using 50% N2O in oxygen and volatile agents. Blood pressure, mean arterial pressure, heart rate, rate pressure product and side effect were recorded at 0.4 and 6 minutes. The data was analyzed using Studentâs t-test and Chi-square at the significance of p<0.05. The results of the study showed that the dose of fentanyl of 2 ug/kgwb iv could change the rate pressure product (RPP) as compared to the fentanyl 1 ug/kgwb iv after fentanyl, intubation and 3 minutes after intubation. The measurement was conducted after the fentanyl (minute 4) and there was not any significant difference between the two groups p>0.05 (p = 0.154), while there was a significant difference between the two groups p<0.05 after the intubation (minute 6) and 3 minutes after the intubation (minute 8). The measurement after the intubation (minute 6) of the 60 patients showed that there was only 4 patients of the 60 patients (6.7%) who had the unstable RPP value with the fentanyl 2 ug/kgwb iv, while 60 patients (100%) with fentanyl 1 ug/kgwb iv were indicative of unstable RPP value. The measurement of the 60 patients in 3 minutes after the intubation (minute 8) showed that there were only 12 patients (20%) that had the unstable RPP value with the fentanyl 2 ug/kgwb, while the 60 patients (100%) with the fentanyl 1 ug/kgwb iv had unstable RPP value. Conclusion: the use of the fentanyl 2 ug/kgwb intravena with the propofol 2 mg/kgwb induction was more effective in reducing the hemodinamic response of the increse in the rate pressure product (RPP) as compared to the fentanyl 1 ug/kgwb intravena as a result of the endotracheal intubation.